Inactivation of Latent HIV-1 Proviral DNA Using Clustered Regularly Interspaced Short Palindromic Repeats/Cas9 Treatment and the Assessment of Off-Target Effects - Xu, Yufan; Peng, Xiaorong; Zheng, Yanghao; Jin, Changzhong; Lu, Xiangyun; Han, Dating; Fu, Haijing; Chen, Chaoyu; Wu, Nanping (Frontiers in Microbiology, 2021)
Viral DNA integrated in host cells is a major barrier to completely curing HIV-1. However, genome editing using the recently developed technique of clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 has the potential to eradicate HIV-1. The present study aimed to use a lentiviral vector-based CRISPR/Cas9 system combined with dual small/single guide RNAs (sgRNAs) to attack HIV-1 DNA in the latency reactivation model J-Lat 10.6 cell line and to assess off-target effects using whole-genome sequencing. We designed 12 sgRNAs targeting HIV-1 DNA, and selected high-efficiency sgRNAs for further pairwise combinations after a preliminary evaluation of the editing efficiency. Three combinations of dual-sgRNAs/Cas9 with high editing efficiency were screened successfully from multiple combinations. Among these combinations, the incidences of insertions and deletions in the sgRNA-targeted regions reached 76% and above, and no credible off-target sites were detected using whole genome sequencing. The results provided comprehensive basic experimental evidence and methodological recommendations for future personalized HIV-1 treatment using CRISPR/Cas9 genome editing technology.